Regulation of gastric emptying in humans by cholecystokinin. - Liddle, R A (1986)
In the present study we used a bioassay system for measuring plasma cholecystokinin (CCK) to evaluate whether CCK has a physiologic role in regulating gastric emptying in humans. Plasma CCK levels and gastric emptying after ingestion of a mixed liquid meal were determined in five normal male volunteers. Fasting CCK levels averaged 0.8 +/- 0.1 pM and increased to 6.5 +/- 1.0 pM within 10 min of drinking the mixed meal. CCK levels remained elevated for up to 90 min. Gastric emptying after a meal was slow; at the end of the 90 min 68% of the original volume remained in the stomach. The rate of gastric emptying of water was then measured in the same individuals with a simultaneous infusion of either saline, or one of two doses of CCK (12 pmol/kg per h and 24 pmol/kg per h). With the saline infusion, plasma CCK levels did not increase above basal and gastric contents emptied rapidly. At the end of 90 min only 7% of the original volume remained in the stomach. The lower dose of CCK resulted in a plasma level of 3.4 pM which both reproduced the average postprandial plasma level and caused a significant delay in gastric emptying. The higher dose of CCK achieved plasma levels of 8 pM and resulted in a delay in gastric emptying that was similar to that seen with the mixed meal. Since exogenous CCK at concentrations which occur postprandially delays gastric emptying, we conclude that CCK is a physiologic regulator of gastric emptying.